OPEN QUANTUM SYSTEMS CONSIDERATION OF INTERACTION HARMONIC OSCILLATOR QUANTUM BATTERY-CHARGER MODEL WITH STEP FUNCTION APPROACH - Gede Agus Krisna Yogantara, Putu
Analysis has been carried out on the interaction model of charger and quantum batteries. The energy replenishment process was analyzed using the open quantum system approach. Models of charger and quantum batteries use harmonic oscillator models. This model was chosen because this model is able to provide greater energy when compared to other battery models. The dynamics of the interaction are determined using the master equation Lindblad Master Equation by generating the equation of motion from the harmonic oscillator operator charger-battery with the constant dephasing using the ladder function approach. The energy equation is obtained by solving the equation of motion to obtain the first momenta of the operator. The calculation and modeling results show that in region I there is an interaction in close system and in region II there is an interaction in open system. In the interaction in region II, the energy produced is greater as a result of the assistance of interaction with the environment. So it can be said that quantum batteries have a better impact than conventional batteries.